Pengaruh Kepercayaan dan Kualitas Pelayanan Nasabah terhadap Kepuasan Perusahaan Bank Syariah Indonesia Cabang Pontianak - Zulfan Asrari; M. Khairul Anwari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study was to determine the trust and quality of customer service towards the satisfaction of the Bank Syariah Indonesia Pontianak Branch. The population in this study were customers, with a sample of 100 people. Determination of sample withdrawal using incidental sampling techniques. Determination of the sample size of the research object using the Slovin formula with a confidence level of 90% (significance level of 0.10). Slovin formula with a confidence level of 90% (significance level of 0.10) / Data collection techniques using questionnaire distribution techniques. Based on the results of the analysis and discussion that have been carried out, it can be concluded that the characteristics of respondents in this study show that respondents who are customers of BSI Pontianak Branch show that most customers are aged 19-28 years, last education is high school / vocational school, civil servant jobs, male, are customers of BSI Pontianak Branch 100%.